PENYESUAIAN DIRI PEREMPUAN DALAM PERSPEKTIF KEBUDAYAAN: Analisis Tokoh Anju dan Sudha dalam Novel Sister of My Heart dan The Vine of Desire Karya Chitra Banerjee Divakaruni - Fatma Hetami (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2007)
Personal adjustment which is derived from cultural system and social interactions always becomes an actual issue. Likewise, the description of women’s personal adjustment which is reflected through the character of Anju and Sudha in Sister of My Heart and The Vine of Desire written by Chitra Banerjee Divakaruni. The result of the analysis indicates that the description of women’s personal adjustment reflected through the character of Anju and Sudha in Sister of My Heart and The Vine of Desire is influenced by cultural setting in the plot of the novel. Cultural interaction carried out by Anju and Sudha has produced typical different patterns of personal adjustment. In India, Anju and Sudha tend to adjust themselves allopathically, while in America, they tend to adjust themselves autopathically. The typical different patterns of personal adjustment produced by Anju dan Sudha can be seen clearly through the analysis of several factors, such as steps of (1) personal development, (2) conflicts experienced by the characters, and (3) women position in a certain culture.